(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The article deals with the issues of toponymic research in the linguoculturological aspect. Special attention is paid to the origin, etymology and history of place names in Great Britain. The structural and semantic analysis of toponyms is given, the historical features of the development of the English language that influenced geographical proper names are revealed, their classification is given in accordance with etymology